Aesthetic Reconstruction of the Frontotemporal Region: The Extended A-T Plasty, A Workhorse Revisited. Issue 1 (July 2017) - Brunetti, Beniamino; Tenna, Stefania; Poccia, Igor; Segreto, Francesco; Persichetti, Paolo
Abstract : Background: A-T plasty has long been a workhorse for defects located around the eyebrow or in the upper and lower lip. It allows like-with-like reconstruction with placement of the scars in natural creases or subunit junctions. In this article, the authors describe their refined technique to specifically address moderate to large size defects of the frontotemporal, preauricular, and zygomatic regions. Materials and Methods: Thirty consecutive patients underwent reconstruction with the extended A - T plasty at our institution after skin cancer excision. Mean age at surgery was 63 years (range, 39–87 years). Mean defect size was 5.2 × 4.7 cm. The defects were located in the frontotemporal (13), upper preauricular (10), and zygomatic (7) facial subunits. Results: Mean operative time was 65 minutes. Three (10%) patients suffered from delayed healing at the T junction, with no impairment in the long-term follow-up. All the other flaps healed uneventfully with optimal long-term cosmetic and functional restoration. Follow-up ranged from 3 months to 3 years (mean, 19 months). Conclusions: The basic principles of the A-T plasty were applied to design large advancement-rotation flaps incorporating frontotemporal and preauricular cervicofacial skin. The resulting extended A - T plasty proved to be a simple, reliable, and reproducible technique to resurface, in a "like with like" fashion, moderate to large defects located in the frontotemporal, preauricular and zygomatic facial subunits.